Missing, Punishing, & Pushing Kids Out: Manitoba Education Policy Enactment and the Marginalization of Indigenous Youth in Child Welfare - Mayor, Christine; Hathout, Samir; Janzen, Melanie D. (Critical Education, 2025)
The intersecting colonial systems of child welfare and education overdetermine experiences of educational exclusion of Indigenous children in Manitoba. A fictionalized case vignette is used to depict how settler colonialism, carcerality, and anti-Indigenous racism play out in the lives of students with child welfare involvement. Using critical thematic analysis, we analyze reports from the Manitoba Advocate for Children and Youth on the lives and deaths of two Indigenous children, focusing on the role of discretionary education policy enactment. Four themes are explored: racist constructions of the “problem child;” use of exclusionary discipline; being missed from and missed at school; and an ethical responsibility to care rooted in the Cree conceptualization of wâhkôhtowin. Examples of different policy enactment to better support Indigenous students with child welfare involvement are provided through a reimagined case vignette, with a call to educators to center ethical responsibilities of care for children as their primary duty.